The role of initiator tRNA I met in fidelity of initiation of protein synthesis - Monajemi, H.; Abdullah, W.A.T.W.; Zain, Sharifuddin Md; Daud, M.N.; Omar, N.Y.M. (2011)
The proper arrangement of amino acids in a protein determines its proper function, which is vital for the cellular metabolism. This indicates that the process of peptide bond formation requires high fidelity. One of the most important processes for this fidelity is kinetic proofreading. As biochemical experiments suggest that kinetic proofreading plays a major role in ensuring the fidelity of protein synthesis, it is not certain whether or not a misacylated tRNA would be corrected by kinetic proofreading during the peptide bond formation. Using 2-layered ONIOM (QM/MM) computational calculations, we studied the behavior of misacylated tRNAs and compared the results with these for cognate aminoacyl-tRNAs during the process of peptide bond formation to investigate the effect of nonnative amino acids on tRNAs. The difference between the behavior of initiator tRNA i met compared to the one for the elongator tRNAs indicates that only the initiator tRNA i met specifies the amino acid side chain. Copyright © Taylor and Francis Group, LLC.